STUDI KOMPARATIF PERCERAIAN AKIBAT PINDAH AGAMA MENURUT FIKIH ISLAM DAN UNDANG-UNDANG PERKAWINAN (Analisis Putusan No. 0879/Pdt. G/2013/PA.Pdg) - Imanda Putri Andini (Universitas Muhammadiyah Sumatera Utara, 2017)
According to Islamic law, if one party of couple converts, the marriage of both becomes void, but in Laws Number 1/1974, there is no specified that the conversion of religion as the reason for the breaking of marriage, so that in Decision Number 0879/Pdt.G/2013/PA.Pdg, which examines the divorce suing for reasons of conversion, decided for reasons there is no harmony in the household . It is certainly interesting to analyze, and based on the analysis it can be seen that the judges postulate convert only as one of the triggers of the existence of unreliability in the household.